Dietary high lipid and high plant-protein affected growth performance, liver health, bile acid metabolism and gut microbiota in groupers - Jia Xu; Fan Wang; Chaoqun Hu; Junxiang Lai; Shiwei Xie; Kefu Yu; Fajun Jiang (Animal Nutrition)
High lipid diets (HLD) and high plant-protein diets (HPD) exhibit potential fishmeal-saving effects but negatively impact liver health and growth performance in fish. We hypothesized that HLD and HPD impair liver health in pearl gentian groupers (Epinephelus fuscoguttatus♂ × Epinephelus lanceolatus♀) through the modulation of intestinal microbiota and bile acid (BA) metabolism. Four diet groups were tested: control diet (CD, 46.21% crude protein, 9.48% crude lipid), HLD (46.37% crude protein, 16.70% crude lipid), HPD (46.50% crude protein, 9.38% crude lipid), and high lipid-high plant-protein diet (HLPD, 46.54% crude protein, 16.67% crude lipid). A total of 300 fish (average body weight = 15.22 ± 0.03 g) were randomly divided into 4 diet treatments (ensuring 3 tanks replicates of each diet treatment, each tank containing 25 fish). After an eight-week feeding period, the HLD and HPD significantly decreased the final body weight (FBW), weight gain rate (WGR), specific growth rate (SGR) and feed intake (FI) in comparison to CD group, with HLPD exacerbating these indicators (P < 0.05). Compared to CD group, the content of total cholesterol (T-CHO) and triglyceride (TG) in liver and serum were significantly increased in HLD group (P < 0.05). Compared to HPD group, the content of T-CHO in liver was significantly decreased, the content of TG in liver and serum were significantly increased in HLPD group (P < 0.05). HLD, HPD, and HLPD impaired liver health by inducing histological damage, inflammation, and oxidative stress. Compared to CD group, the mRNA relative expression of bile salt export pump (bsep) and multidrug resistance protein 3 (mdr3) were significantly increased in HLD group, whereas the mRNA relative expression of sterol-27-hydroxylase (cyp27a1), microsomal epoxide hydrolase (meh), apical sodium-dependent bile acid transporter (asbt), multidrug resistance-associated protein 3 (mrp3), farnesoid X receptor (fxr) and G protein-coupled bile acid receptor 5 (tgr5) were significantly decreased (P < 0.05). Compared to CD group, the mRNA relative expression of mdr3, asbt, mrp3, organic anion transporters 1 (oatp1), meh, fxr and tgr5 were significantly decreased in HPD group (P < 0.05). In summary, HLD affects intestinal microbiota, BA metabolism, and lipid metabolism, leading to lipid deposition and liver damage. HPD regulates gut microbiota, BA metabolism, inflammatory responses, and BA receptor expression, impairing grouper liver health. HLPD synergistically combines the adverse effects of HLD and HPD on grouper liver health.